El Excentrico, 1981-01-01 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2024)
April 1981 [Abril de 1981]. No volume or issue number. Cover contains a picture of Juanita Quintania in flapper attire, who had been given the Queen of the Lucha Villa Fan Club title. The cover serves as an advertisent for a roaring twenties themed dance hoste by the Lucha Villa Fan Club.